PENGARUH CELEBRITY ENDORSER, KUALITAS PRODUK, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PRODUK BODY LOTION SCARLETT WHITENING - Damayanti, Alvina; Inayati, Titik (BISMA: Jurnal Bisnis dan Manajemen, 2024)
In the beauty industry, facial and body care is a major need for women to have an attractive and special appearance. This research aimed to 1) test and analyze the influence of celebrity endorsers on purchasing decisions for Scarlett Whitening body lotion products; 2) test and analyze the influence of product quality on purchasing decisions for Scarlett Whitening body lotion products; and 3) test and analyze the influence of word of mouth on purchasing decisions Scarlett Whitening body lotion product. The population in this study were 299 students from the Faculty of Economics and Business from the Management Study Program at Wijaya Kusuma University, Surabaya. The sampling technique used a non-probability sampling method with purposive sampling. The sample determined was 171 respondents with criteria: 1) respondents have seen advertisements for Scarlett Whitening body lotion products, and 2) respondents have repurchased Scarlett Whitening body lotion products at least 2 times. Data was collected by distributing questionnaires and analyzed using the normality test, coefficient of determination test, multiple linear regression analysis, T test. SPSS version 20 for Windows was then operated as analysis tools. The research results show that celebrity endorsers do not have a significant influence on purchasing decisions. Meanwhile product quality and word of mouth has a significant influence on purchasing decisions.